PENGARUH MATA KULIAH KEWIRAUSAHAAN DAN PELATIHAN WIRAUSAHA TERHADAP MINAT BERWIRAUSAHA EKONOMI KREATIF PADA MAHASISWA UNIVERSITAS ISLAM OKI (UNISKI) KAYUGUNG - Fernandes, Ari (MOTIVASI, 2020)
Purpose - This research was conducted on students of FKIP IslamicUniversity OKI (UNISKI) Kayuagung. Unicorn students are required totake entrepreneurship courses and almost all attend creativeentrepreneurship training that is regularly held. This research will answerthe question whether the provision of courses and training can increasetheir entrepreneurial interest in the creative economyStock Exchange. Design/methodology - The sample of this study consisted of 100students from Fikip Unsiki who were taken at random. The regressionmodel of this study is: Yi = a + b1X1 + b2X2Where :Yi is interested inbeing a creative entrepreneur. i is an indicator of creativeentrepreneurial interest. Namely: 1. The desire to work independently,2. The desire to obtain challenges, 3. The desire to obtain a fluctuatingincome and not small but stable, and 4. The desire to create somethingnew. Each indicator is given a value on a scale of 5. Findings - The test results show that: 1) Entrepreneurship courses havea positive effect on the creative entrepreneurial interests of IslamicUniversity OKI students. 2) Entrepreneurship training has a positiveeffect on UNISKI students' creative entrepreneurial interests